Factors Influencing Adherence to Non-Invasive Telemedicine in Heart Failure: A Systematic Review - George Koulaouzidis; Lamprini Tsigkriki; Orestis Grammenos; Sotiria Iliopoulou; Maria Kalaitzoglou; Panagiotis Theodorou; Ioannis Bostanitis; Karolina Skonieczna-Żydecka; Dafni Charisopoulou (Clinics and Practice)
Background/Objectives: Telemedicine (TM) has emerged as a promising tool for improving heart failure (HF) management by allowing non-invasive, remote patient monitoring. However, patient adherence to TM plays a critical role in its effectiveness. This systematic review aims to assess adherence levels to non-invasive TM interventions and explore factors influencing compliance. Methods: This systematic review followed the PRISMA guidelines. A literature search was conducted across the PubMed, Medline, Web of Science, and Google Scholar databases to identify prospective randomized controlled trials published between January 2010 and June 2024. The inclusion criteria included studies focused on non-invasive TM in HF patients with a follow-up period longer than three months. Adherence rates were categorized as high (≥80%), moderate (60–79%), or low (<60%). Results: Of the 136 identified studies, 6 met the inclusion criteria. Three studies reported high adherence (>80%), and three moderate adherence (60–79%). Older patients (≥65 years) showed higher adherence, with two studies exceeding 85% adherence. Studies with higher female participation (>30%) reported better adherence, with two exceeding 88%. Across studies, a lack of racial diversity was especially notable, apart from a study that included a population with 69% black and 31% Hispanic participants, where adherence was 50% for ≥10 uploads over a 90-day period. Seasonal variations affected adherence, with December being the lowest (47–69%) and August the highest (>85%). Monitoring multiple health parameters correlated with better adherence (>85%) compared to single-parameter tracking (50–74%). Conclusions: TM is a promising tool for HF management, but adherence differs by age, sex, and the complexity of monitoring. To optimize TM use, standardized adherence measures and tailored strategies are needed.